Evaluation of Antioxidant, Immunomodulatory, and Cytotoxic Action of Fractions from Eugenia uniflora L. and Eugenia malaccensis L.: Correlation with Polyphenol and Flavanoid Content - Evellyne de Oliveira Figueirôa; Luís Cláudio Nascimento da Silva; Cristiane Moutinho Lagos de Melo; Juliana Kelle de Andrade Lemoine Neves; Nicácio Henrique da Silva; Valéria Rêgo Alves Pereira; Maria Tereza dos Santos Correia (The Scientific World Journal)
An increasing number of biological activities presented by medicinal plants has been investigated over the years, and they are used in the search for new substances with lower side effects. Eugenia uniflora L. and Eugenia malaccensis L. (Myrtaceae) have many folk uses in various countries. This current study was designed to quantify the polyphenols and flavonoids contents and evaluate the immunomodulatory, antioxidant, and cytotoxic potentials of fractions from E. uniflora L. and E. malaccensis L. It was observed that the polyphenol content was higher in ethyl acetate fractions. These fractions have high antioxidant potential. E. malaccensis L. seeds showed the largest DPPH radical scavenger capacity (EC50=22.62). The fractions of E. malaccensis L. leaves showed lower antioxidant capacity. The samples did not alter the profile of proinflammatory cytokines and nitric oxide release. The results indicate that species of the family Myrtaceae are rich in compounds with antioxidant capacity, which can help reduce the inflammatory response.